AYURVEDIC ACCESS TOWARDS HYPOMENORRHOEA - Sarmah, *Smita; Baishya, Balen (International Journal of Ayurveda and Pharma Research, 2017)
Every creation of God is made of so many systems like gastrointestinal system, respiratory system, cardiovascular system, reproductive system etc. Stability of every system and its contents are very important for maintaining a healthy lifestyle. A proper balanced menstrual cycle is the result of a balanced reproductive system. In Ayurveda also is it is mentioned that equilibrium condition of Agni, Dhatu, Mala etc can make a person healthy both physically and mentally. Disturbance in menstruation in any form can affect a woman both physically and mentally. Hypomenorrhoea is a menstrual condition where menstrual cycle is disturbed due to various factors. Hormonal imbalance, stress, local cause, defect in H- P-O axis etc can lead to any menstrual deformity. At the beginning of hypomenorrhoea, treatment should be started so that it can be resolved easily and in short period of time. Ayurvedic treatment can be done to treat the condition. For this condition also, treatment should be done with a aim to normalize the vitiated Dosha and Dhatu. Scanty Artava is seen in this condition and treatment is done for increasing Artava. By taking some diet containing some useful ingredients in day to day life can heal the condition. So, in this topic the Ayurvedic way to treat hypomenorrhoea is discussed concisely.